Revealing the mechanistic interactions of profenofos and captan pesticides with serum protein via biophysical and computational investigations - Kamonrat Phopin; Waralee Ruankham; Supaluk Prachayasittikul; Virapong Prachayasittikul; Tanawut Tantimongcolwat (Scientific Reports, 2024)
Abstract Profenofos (PF) and captan (CT) are among the most utilized organophosphorus insecticides and phthalimide fungicides, respectively. To elucidate the physicochemical and influential toxicokinetic factors, the mechanistic interactions of serum albumin and either PF or CT were carried out in the current study using a series of spectroscopy and computational analyses. Both PF and CT could bind to bovine serum albumin (BSA), a representative serum protein, with moderate binding constants in a range of 103–104 M−1. The bindings of PF and CT did not induce noticeable BSA’s structural changes. Both pesticides bound preferentially to the site I pocket of BSA, where the hydrophobic interaction was the main binding mode of PF, and the electrostatic interaction drove the binding of CT. As a result, PF and CT may not only induce direct toxicity by themselves, but also compete with therapeutic drugs and essential substances to sit in the Sudlow site I of serum albumin, which may interfere with the pharmacokinetics and equilibrium of drugs and other substances causing consequent adverse effects.